Evaluation of adherence to an evidence-based bundle of care for the treatment of staphylococcus aureus bacteraemia at Groote Schuur Hospital - Gatley, Elizabeth M (Department of Medicine, 2023)
Background Staphylococcus aureus bacteraemia (SAB) is associated with high hospital mortality. Improvements in outcome have been described with standardised bundles of care. Objectives To study adherence to a standardised bundle of care (BOC) recommendations using a consultation proforma, for all patients admitted with SAB to Groote Schuur hospital over a year. To describe in-hospital and 90-day mortality in these patients Methods A retrospective audit of all unsolicited infectious disease consultations for patients with SAB admitted to Groote Schuur hospital during 2018. Adherence to recommendations of a standard care bundle were audited. Results Eighty six patients were included; 61 (71%) with healthcare-associated infection and 25 (29%) with community associated infection. Over 80% of adherence to treatment recommendations was achieved regarding antibiotic (including vancomycin) usage, source control and use of echocardiography as required. In-hospital mortality was 16% while overall 90-day mortality was 18%, with only age an independent predictor of mortality. No association with adherence to the recommendations and outcome was seen. Conclusion Adherence to a simple BOC is good, when using standardised a proforma as a communication tool. SAB mortality may be reduced by such an approach.